2013
DOI: 10.1039/c3ja50110h
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in instrumentation of microwave plasma sources for optical emission and mass spectrometry: Tutorial review

Abstract: This paper reviews the most common methods of generation of plasmas using microwaves with special emphasis on recently developed microwave plasma (MWP) sources for analytical applications. The art and science of microwave plasma optical and mass spectroscopy instrumentation (MWP-OES/MS), and the applications are briefly presented, including very recent advances in the field as of 2012. The design and operation of MWPs is discussed to provide a basic understanding of the most important selection criteria when d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 117 publications
(166 reference statements)
0
17
0
Order By: Relevance
“…While other plasma sources and types have been developed and tested (Montaser et al . , Jankowski and Reszke ), commercial hardware is focused solely on instruments using argon‐based ICP. Recently, however, a commercial microwave plasma (MP) AES system has been introduced onto the market, which appears to provide an attractive alternative to flame AAS and ICP‐AES.…”
Section: Advances In Plasma Source Emission Spectroscopy (Contributiomentioning
confidence: 99%
See 2 more Smart Citations
“…While other plasma sources and types have been developed and tested (Montaser et al . , Jankowski and Reszke ), commercial hardware is focused solely on instruments using argon‐based ICP. Recently, however, a commercial microwave plasma (MP) AES system has been introduced onto the market, which appears to provide an attractive alternative to flame AAS and ICP‐AES.…”
Section: Advances In Plasma Source Emission Spectroscopy (Contributiomentioning
confidence: 99%
“…Developments in instrumentation for MP sources have been reviewed by Jankowski and Reszke (). Historically, plasmas have used the energy from microwave electric field, leading to very thin, rodlike plasmas.…”
Section: Advances In Plasma Source Emission Spectroscopy (Contributiomentioning
confidence: 99%
See 1 more Smart Citation
“…Among other plasma sources, some interesting multi-electrode approaches of plasma powered by rotating fields have been reported, operating under different regimes including electrode arrangement and operating conditions such as power, frequency and gas flow. [12][13][14][15][16][17] Jankowski et al demonstrated that rotating field discharges operating at the kHz level could be analytically useful for determination of gaseous samples. 16,17 In the present work, a novel, on-line hyphenated system based on ultrasonic nebulization and photo-induced chemical vapor generation with digitally controlled rotating field plasma-optical emission spectrometry was developed and evaluated for the determination of mercury (USN-UV-CVG-RFP-OES).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma sources including microwave plasmas (MWPs) have played an important role as radiation/ionization sources for atomic and molecular spectrometry. [12][13][14] The argon or helium microwave induced plasma (Ar-MIP or He-MIP) is commonly sustained at the atmospheric pressure in one-tube quartz or ceramic torches using cylindrical Beenakker resonant cavities, e.g., operated in TM010 modes, and surfactants. In recent years, compact helium plasma sources operating at atmospheric pressure have been of great importance in optical emission spectrometry (OES) as well as in mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%